Social Evolution, Political Psychology, and the Media in Democracy The Invisible Hand in the U.S. Marketplace of Ideas - Beattie, Peter (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
X, 363 p. 1 illus.